2021
DOI: 10.2147/ott.s278986
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA DDX11-AS1 Exerts Oncogenic Roles in Glioma Through Regulating miR-499b-5p/RWDD4 Axis

Abstract: Background: Long noncoding RNAs (lncRNA) exert essential functions during tumorigenesis. However, how lncRNAs participate in glioma development remains poorly researched. This study aimed to determine how DDX11-AS1 affects glioma progression. Methods: Gene expression was analyzed by qRT-PCR. Survival rate curve was plotted in 56 glioma patients. Loss-of-function assays were performed to analyze proliferation, migration, and invasion through CCK8, colony formation, and transwell assays. Luciferase assay and RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…It is involved in several signaling pathways such as tumor cell proliferation, migration, and invasion. It acts as an miRNA sponge, targeting in particular miR-499b-5p which is involved in the regulation of the expression of the GBM oncogene RWDD4 ( Zheng et al, 2021 ).…”
Section: The Non Coding Rnamentioning
confidence: 99%
“…It is involved in several signaling pathways such as tumor cell proliferation, migration, and invasion. It acts as an miRNA sponge, targeting in particular miR-499b-5p which is involved in the regulation of the expression of the GBM oncogene RWDD4 ( Zheng et al, 2021 ).…”
Section: The Non Coding Rnamentioning
confidence: 99%
“…The research reports that DDX11-AS1 is highly expressed in the cytoplasm of glioma cells. 25 Moreover, increasing studies have shown that lncRNA regulation of cell function in the cytoplasm depends on proteins. 26 , 27 Therefore, to explore the potential binding proteins of DDX11-AS1, we predicted the binding RBPs of DDX11-AS1 on starBase v.2.0, and the results showed that DDX11-AS1 can bind 43 RBPs.…”
Section: Resultsmentioning
confidence: 99%
“…find that the DDX11-AS1/mir-499B-5p/RWDD4 axis promotes the proliferation of glioma cells. 25 However, the potential other molecular mechanisms of DDX11-AS1 in glioma are poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that DDX11-AS1, as a novel lncRNA, played an imperative function in the progression and metastasis in multiple cancers, including glioma [ 47 ], bladder cancer [ 21 , 22 ], gastric cancer [ 17 , 18 ], hepatocellular carcinoma [ 15 ], and so on [ 14 , 19 , 20 , 23 ]. In the current research, the DDX11-AS1 functions, as well as molecular mechanisms in EMT process of ESCC, were further explored.…”
Section: Resultsmentioning
confidence: 99%